Pemetaan Tingka Kebisingan Pada Pemukiman Sekitar Rel Kereta Api di Kota Bekasi - Fitriani, Fitriani; Miarsono, Harry; Hidayatullah, Syarif; Pratama, Ardi (JURNAL TEKNIK SIPIL, 2025)
The expansion of Jakarta’s suburban areas has intensified residential development near railway lines, including Bekasi City, West Java. High-frequency train operations generate noise levels that may exceed the residential environmental quality standard of 55 dB(A) stipulated by Indonesia’s Ministry of Environment Decree No.48/1996. This study aims to measure noise levels, map their spatial distribution, and propose mitigation strategies. Measurements were conducted using a Sound Level Meter (SLM) at ten sampling points on both sides of the railway, spaced approximately 400 meters apart. Data were collected over two weeks during peak hours, with readings recorded every 5 seconds for 10 minutes at each point. Results indicate average daily noise levels of 60–65 dB(A), with the highest value of 75 dB(A) at approximately 3 meters from the track and the lowest value of 52 dB(A) beyond 15 meters. Noise mapping using Surfer 15.0 and ArcGIS 10.2 shows critical zones >70 dB(A) within a 0–5 meter radius, while zones of 60–70 dB(A) dominate 5–10 meters. Levels below 55 dB(A) occur only beyond 15 meters and are rare due to high housing density. Recommended mitigation includes natural barriers such as dense vegetation, artificial barriers such as acoustic panels, and enforcing a minimum 20-meter setback for new housing development. This study underscores the importance of noise mapping as a foundation for spatial planning and residential environmental protection.